Overview of Grounding System Improvements: Design, Simulation, Grounding Enhancement Materials - Abubakar, Banjo; Chin Leong, Wooi; Shing Fhan, Khor; NIK HAKIMI, NIK ALI; Yi Lung, Then; Hadi Nabipour, Afrouzi (2025)
Grounding systems are essential for dissipating electrical discharges, preventing equipment damage and human casualties from lightning strikes. Traditional grounding methods using steel or copper rods face challenges in highresistivity soils and space-limited areas. Alternatives like Ufer grounding depend on soil moisture, while Ground Enhancement Materials (GEMs) like bentonite improve conductivity but raise cost and environmental concerns. Advancements in simulation tools and testing methodologies have enhanced grounding system design, enabling precise resistance predictions and corrosion detection. This review explores recent innovations in GEMs, modeling techniques, and performance assessments, emphasizing the shift toward safer, more efficient, and sustainable grounding solutions.